Dermoscopy in the diagnosis of selected inflammatory dermatoses - Aleksandra Fijałkowska; Magdalena Wojtczak; Agnieszka Żebrowska (Termedia Publishing House, 2023)
Dermoscopy was initially used as a non-invasive method for differentiation of pigmented lesions and skin cancers. In recent years, its use goes far beyond the area of dermato-oncology and is recognized as an effective technique in the diagnosis of many inflammatory dermatoses. The clinical similarity of these diseases often requires histopathological examination, an invasive and time-consuming technique. Dermoscopy (inflammoscopy) allows for the visualization of structures typical for individual inflammatory skin disorders. Thus it became key diagnostic tool in the daily practice of every dermatologist. We present in this article the use of inflammoscopy in selected inflammatory skin diseases: psoriasis, lichen planus, eczema and pitiriasis rosea.